Data independent acquisition reveals in-depth serum proteome changes in uremic pruritus - Wen-Jing, Zhao; Rui-Zhi, Tan; Si-Yuan, He; Xiao-Mei, Du; Qiong-Dan, Hu; Xiao-Qian, Zhang; Wen-Hua, Huang; Hong-Wei, Su; Jian, Liu; Qiong, Zhang; Li, Wang (Frontiers in Physiology, 2024)
Introduction: Uremic pruritus (UP) is a prevalent symptom in patients suffering from uremia, yet its underlying etiology and mechanisms remain incompletely elucidated. Given the significant incidence of UP, identifying specific alterations in proteins present in the blood of UP patients could offer insights into the potential biological pathways associated with UP and facilitate the exploration of biomarkers. Methods: In this study, we employed LC-MS/MS-based data-independent acquisition (DIA) mode to analyze serum samples obtained from 54 UP patients categorized as DKD-UP, HN-UP, and GN-UP (n = 18 for each subgroup), along with 18 uremic patients without pruritus (Negative) and 18 CKD patients without pruritus (CKD). Through DIA mode analysis, a total of 7075 peptides and 959 proteins were quantified. Within these, we identified four upregulated and 13 downregulated Differentially Expressed Proteins (DEPs) in DKD-UP versus Negative, five upregulated and 22 downregulated DEPs in HN-UP versus Negative, and three upregulated and 23 downregulated DEPs in GN-UP versus Negative. Furthermore, we conducted an intersection analysis of the DEPs across these three comparison groups to derive a set of common DEPs (COMP). Subsequently, a total of 67 common DEPs were identified in the three UP groups when compared to the CKD group, with 40 DEPs showing upregulation and 27 DEPs displaying downregulation. Results: Following Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Protein-Protein Interaction (PPI) analyses, we observed that the DEPs distinguishing UP from CKD were primarily associated with mitochondrial function (MT-CYB, PRDX2, TOMM22), inflammation (CD59, CSF1), renal injury (WFDC2), and neural function (CAP1, VGF). Discussion: Our findings contribute to a potential molecular comprehension of UP pathogenesis, shedding light on the identification of these DEPs as plausible biomarkers for UP.